Perceptions and use of technology to support self-management for older adults living with multiple health conditions within an ecosystem of care - Dinsmore, John; Murphy, Emma; Hannigan, Caoimhe; Smith, Suzanne; Doyle, Julie (My University, 2017)
In this study we have explored what technologies older people with multimorbidity (PwMs) are currently using and how they and their networks of care perceive technology to support their health conditions. This research is part of ProACT - an EU-funded Horizon 2020 project that aims to develop and evaluate a digital integrated care ecosystem to support older people with multimorbidity (PwM). This study is part of an extensive user requirements study to elicit requirements for the design of the digital care system. While older adults generally have positive opinions and attitudes towards trying and using new technologies (Mitzner et al., 2010), health status itself is a moderating factor for computer use and digital literacy (Heart and Kalderon, 2013).
Irish Gerontological Society 65th Annual and Scientific Meeting
Keywords: Digital Health; Multimorbidity; Chronic disease; Self-management; Older adults; Behavioural Change; Ageing; Digital Engagement; ASSISTIVE TECHNOLOGY; Behavioural Change; Behavioural change interventions; Chronic Disease Management; Chronic disease self-management; Digital Behavioural Change Interventions; Digital Health; OLDER PERSONS; multimorbidity; Age-related disability; Chronic Health Condition; Health